Do dialogismo ao letramento: perspectivas para a leitura significativa na EJA - Santos, Cássia Oliveira (2008)
This work is in search line of Reading, Writing and Teaching of the Portuguese language and has as theme the study of the expansion of the degree of literacy of a person that is already literate in the Student Elementary School II of the Youth and Adults Education (YAE), through the teaching of meaningful reading, developed under school. We have as a central objective to contribute to the studies of the literacy associating it to dialogical studies and enunciates of Mikhail Bakhtin and Paulo Freire, who understand the interaction between the person s discourse and the world. We have as specific objectives to contribute to the teaching of meaningful reading, developed in the Portuguese Language classes, taught for the students (YAE), and contribute to the teaching of meaningful reading in State School, an institution in which we work and where we believe that we can develop a work dedicated to the teaching of that reading. In discussing the importance of an education geared to the meaningful reading in the classroom, we propose an analysis on the statement I love you, based on the context of interaction, the dialogism and the multiplicity of ways. We suggest, also, two activities of reading that, we believe, can be worked in the (YAE), and they consider the social dimension and discursive of language, as well as the literate practices of the involved people in any situation of speech communication. The research enabled us propose a dialogue between the (YAE), studies of literacy and the theoretical principles of Bakhtin and Freire. We, therefore, that proficient reading goes beyond the linguistic code, pure and simple, and it is effective through factors such as the context of interaction, dialogical resources and the multiplicity of ways